Evaluation of in vivo and in vitro Pathogenicity of Aeromonas veronii Isolated from Freshwater Fishes of Andhra Pradesh - Lavanya, Chethurajupalli; Neeraja, Tambireddy; Ramana, Thatavarthi Venkata; Balasubramanian, Arumugum; Lakkoju, Nischal (Fishery Technology, 2025)
Aeromonas spp. are responsible for causing hemorrhagic septicemia resulting in significant mortalities in carp aquaculture. Among the different species, Aeromonas veronii is considered as a significant pathogen and is second only to A. hydrophila in causing severe economic losses to freshwater fish farmers. The present study was carried out to isolate and identify A. veronii from freshwater fishes in Andhra Pradesh, India. In addition, both in vivo and in vitro pathogenicity assays were performed to assess its virulence. A total of 95 A. veronii strains were meticulously isolated from 80 [Labeo rohita (n=40), Catla catla (n=40)] fish samples and subjected to biochemical tests (API 20E system), PCR confirmation (amplification of 16S rRNA gene), and virulence gene profiling. The strains exhibited a genetic diversity ranging from four to eight virulence genes, with a prominent genotype (ahy+, ahp+, enol+, lip+, alt+, hly+) observed in 28% of the isolates. In vivo pathogenicity analysis indicated that 72% of the strains exhibited hemolytic activity, which was strongly associated with the presence of aer+, hly+, and ahyB+ genes. Furthermore, in vivo challenge experiments demonstrated that even Aeromonas strains with as few as four virulence genes (ahy+, enol+, aer+, alt+) were capable of inducing over 90% mortality. These findings strongly imply that the pathogenicity of A. veronii is more significantly influenced by the synergistic effect of virulence genes rather than their total number. The high virulence of A. veronii poses a serious threat to the freshwater aquaculture, underscoring the need for enhanced monitoring and management strategies.